Pengembangan Media Pembelajaran Matematika Berbasis Budaya Batak Toba - Barus, Despyanti Br (Unika Santo Thomas Medan, 2019)
This study aims to find out how the development of Batak Toba culture-based mathematics learning media with a contextual approach and to find out how effective the development of Batak Toba culture-based mathematics learning media with a contextual approach is. The development of mathematics learning media was prepared using the ADDIE model. The subject of this research is class VII E with a total of 32 students. The type of data used is qualitative data and quantitative data. The first stage is the analysis phase. This stage is done to analyze the needs of research such as researchers conducting observations, interviews, and pretests. The next stage is the design of a mathematics learning media design in the form of Student Activity Sheets (LAS) based on the Toba Batak culture. The third stage is development, at this stage the learning media product is validated by the material expert and media expert validator to obtain the feasibility of the product that has been designed based on the results of the validation and the validator's suggestions and comments. The fourth stage is implementation, at this stage after the mathematics learning media product is validated then the product is tested. The last stage is evaluation, at this stage after the product is tested the final results of the field test in the form of a pretest and posttest are then analyzed and scores are obtained as a result of student learning. Based on the analysis of research data, the following results were obtained: (1) Student Activity Sheet (LAS) based on Toba Batak culture can be used for mathematics learning on the subject of rectangles and triangles in terms of the value given by the material expert and media validator 88% with a very valid and appropriate category to be used to improve student learning outcomes; (2) Increasing student learning outcomes by 56.25% this can be seen from the pretest students who completed as many as 11 people (34.37%) while students who did not complete as many as 21 people (65.63%). From the posttest students who completed as many as 29 people (90.62%) while students who did not complete as many as 3 people (9.38%); (3) The teacher's activities at the 1st and 2nd meetings achieved results (85.23%) and the student activities at the 1st and 2nd meetings achieved results (88.66%). So it can be concluded that student learning outcomes at posttest are higher than at pretest. Thus that mathematics learning media in the form of Student Activity Sheets (LAS) based on the Toba Batak culture are effective for use in improving student learning outcomes.